Providing a Levelling Datum to a Tide Gauge Sea Level Record. Issue 1 (2nd January 2022) - Woodworth, Philip L.
Abstract: A method is described for providing a levelling datum to a sea level record containing hourly heights (or similar) with the use of a second record from a nearby location consisting of high waters only but measured to a known datum. The method is tested using data from a pair of stations in the Thames estuary where there is a predominantly semidiurnal tide. It is then applied to the determination of a datum for an important historical sea level record at Liverpool. The historical background to that important record is explained. The limitations of the method are investigated using data from a pair of stations approximately 50 km apart on the north coast of Wales. This latter case study provides insight into which aspects of the tide contribute to inaccuracies in the method when the stations are some distance apart.